Orders of Trigonometric and Kolmogorov Widths May Differ in Power Scale - Konovalov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present a class of functions for which trigonometric widths decrease to zero slower than the Kolmogorov widths in power scale.